Association Of Thyroid Hormone Level With Severity Of Preeclampsia - Harsh, Prerna; Kumar, Ajay; Soni, Swaranjeet (Journal of Neonatal Surgery, 2025)
Background: Preeclampsia is a major cause of maternal and perinatal mortality globally. Thyroid hormones are essential for a healthy pregnancy, and their dysfunction can increase the risk of preeclampsia. The objective of the study was to correlate thyroid hormone with the severity of pre-eclampsia. Method: This study was designed on 140 clinically diagnosed Preeclamptic women in third trimester of pregnancy which was taken from OPD and IPD of Obstetrics and Gynaecology Department of Maharaja Agrasen Medical College, Agroha. Out of them 70 was mild preeclamptic and 70 was severe preeclamptic women. Thyroid hormone (Serum T3, T4 and TSH) measured by an enzyme-linked fluorescent immunoassay (ELFA). Results: The mean serum T3 and T4 levels were higher in mild preeclampsia compared to severe preeclampsia, but the difference was statistically non-significant (p>0.05). In contrast, the mean TSH level was significantly higher in severe preeclampsia (p<0.05). Gravidity did not significantly affect thyroid hormone levels (P>0.05). Thyroid dusfunction was more prevalent in the severe preeclampsia group, with a higher number of cases showing subclinical and overt hypothyroidism. Conclusion: Our findings suggest a potential association between thyroid dysfunction and the severity of preeclampsia. Thyroid hormone levels could serve as a useful screening marker for assessing the severity of preeclampsia..